Is There a Difference in Credit Constraints Between Private and Listed Companies in Brazil? Empirical Evidence by The Cash Flow Sensitivity Approach - Ghani,Alan Nader Ackel (2015)
This article analyzes the credit constraints, using the cash flow sensitivity approach, of private and listed companies between 2007 and 2010. According to this approach, the econometric results show that the credit constraints are the same for either private or listed companies. This paper seeks to contribute to the literature because the study of credit constraints of private companies based on cash flow sensitivity in Brazil has been rare.